Efektivitas Senam Hipertensi dalam Pengendalian Tekanan Darah - Rista Anindya Nurwidjayanti; Rina Puspita Sari; Rifa Tiara Sari; Siti Nurhasanah; Bahrul Ulum; Arizka Puji Lestari; Tri Ningsih (Kolaborasi: Jurnal Pengabdian Masyarakat, 2026)
Introduction: Hypertension is a primary non-communicable disease and a significant public health challenge in Indonesia. Community-based health promotion is essential for its prevention and management, particularly in areas with limited healthcare access. Objective: This community service project aimed to implement and evaluate the effectiveness of a combined intervention hypertension specific exercise and health education in lowering blood pressure and enhancing knowledge among at-risk community members. Method: The project was conducted in Kampung Bayur, Tangerang, involving 25 participants. It followed a three-stage approach: preparation (community assessment and planning), implementation (two sessions of structured hypertension exercises and interactive health education), and evaluation (comparison of pre- and post-test knowledge scores and blood pressure measurements). Result: The intervention resulted in a notable increase in participants' knowledge, with the average score rising from 69.6 to 83.2. Additionally, a consistent reduction in average blood pressure was observed, from 143.48/88.56 mmHg to 137.72/84.56 mmHg, with all participants showing a decrease. Conclusion: The combination of targeted health education and regular hypertension exercise proves to be an effective, non-pharmacological strategy for blood pressure control at the community level. This approach supports health promotion, prevention, and community empowerment, and is recommended for sustainable implementation with local health cadres.